2000
DOI: 10.1007/s004290050326
|View full text |Cite
|
Sign up to set email alerts
|

Arteether-induced brain injury in Macaca mulatta . I. The precerebellar nuclei: the lateral reticular nuclei, paramedian reticular nuclei, and perihypoglossal nuclei

Abstract: Malaria poses a threat across several continents: Eurasia (Asia and parts of Eastern Europe), Africa, Central and South America. Bradley (1991) estimates human exposure at 2,073,000,000 with infection rates at 270,000,000, illnesses at 110,000,000, and deaths at 1,000,000. Significant mortality rates are attributed to infection by the parasite Plasmodium falciparum, with an estimated 90% among African children. A worldwide effort is ongoing to chemically and pharmacologically characterize a class of artemisini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Prominent neuropathic lesions were restricted primarily to the pons and medulla. In vivo toxicity studies with rats and monkeys also revealed neuropathies in the caudal brain stem (13,14,29,30).In humans treated with the artemisinin drugs, adverse affects directly ascribed to neurotoxicity have yet to be unambiguously demonstrated but may possibly be due to neurodegeneration (3.3% of the cases) (15,25,31,32,44).Recently, we described a new in vitro screening method using primary brain stem cell cultures from the rat (37). We demonstrated that the brain stem cells were selectively sensitive against artemisinin, in contrast to cells from other brain regions, such as the cortex.…”
mentioning
confidence: 99%
“…Prominent neuropathic lesions were restricted primarily to the pons and medulla. In vivo toxicity studies with rats and monkeys also revealed neuropathies in the caudal brain stem (13,14,29,30).In humans treated with the artemisinin drugs, adverse affects directly ascribed to neurotoxicity have yet to be unambiguously demonstrated but may possibly be due to neurodegeneration (3.3% of the cases) (15,25,31,32,44).Recently, we described a new in vitro screening method using primary brain stem cell cultures from the rat (37). We demonstrated that the brain stem cells were selectively sensitive against artemisinin, in contrast to cells from other brain regions, such as the cortex.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] However, there were 2 important differences in the design of these earlier experiments compared with the ones presented here. First, the previous studies quite closely followed the proposed malaria monotherapy regimen, with an artemisinin derivative administered daily for 7 consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…However, in rats, dogs, and rhesus monkeys, arteether and artemether have consistently shown symptomatic and pathological evidence of brainstem neurotoxicity after parenteral administration of high doses over several consecutive days. [4][5][6][7][8][9][10][11][12] There is accumulated evidence that neurotoxicity is dose dependent and host related, and evidence also suggests that neurotoxicity depends on the route of administration. 13 During the last 10 years, detailed in vivo studies consistently demonstrated that artemether also exhibits antischistosomal properties, with the young developmental stages being particularly susceptible.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the half life of AE was significantly prolonged from the first dosing day to the last dosing day after intramuscular AE administrations. The monkey showed moderate neurotoxicity after this intramuscular AE dosing regimen (Petras et al, 1997(Petras et al, , 2000.…”
Section: Half Lives Of Arts In Monkeysmentioning
confidence: 95%
“…Since AE-induced brainstem neuropathology in rhesus monkeys occurred at a minimal dose of 8 mg/kg dosed daily for 14 days (Petras et al, 1997(Petras et al, , 2000, the LONEL of AE was estimated to be 193.8 ng/ml. This estimate is based on our TK analysis conducted by dosing monkeys with AE at 16 mg/kg dosed daily for 14 days which should, based on a number of repeat dosing studies, result in evidence of AE-induced neurotoxicity (Petras et al, 1997;Li et al, 2006bLi et al, , 2007a.…”
Section: Neurotoxicity Induced By Intramuscular Ae In Monkeysmentioning
confidence: 99%